2015
DOI: 10.1371/journal.pone.0141284
|View full text |Cite
|
Sign up to set email alerts
|

Theta Burst Stimulation of the Cerebellum Modifies the TMS-Evoked N100 Potential, a Marker of GABA Inhibition

Abstract: Theta burst stimulation (TBS) of the cerebellum, a potential therapy for neurological disease, can modulate corticospinal excitability via the dentato-thalamo-cortical pathway, but it is uncertain whether its effects are mediated via inhibitory or facilitatory networks. The aim of this study was to investigate the effects of 30Hz cerebellar TBS on the N100 waveform of the TMS-evoked potential (TEP), a marker of intracortical GABAB-mediated inhibition. 16 healthy participants (aged 18–30 years; 13 right handed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 51 publications
7
38
2
1
Order By: Relevance
“…Thus, conclusion in the spatial domain should be taken with caution. A recent study by Harrington and Hammond-Tooke27 found that 30Hz-iTBS at 90% of AMT increased N100 amplitude whereas 30 Hz-cTBS at 80% of AMT (but not at 90%) produced the opposite effect. These results are in contrast with what we observed in the present work and with previous studies using cerebellar TBS7.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, conclusion in the spatial domain should be taken with caution. A recent study by Harrington and Hammond-Tooke27 found that 30Hz-iTBS at 90% of AMT increased N100 amplitude whereas 30 Hz-cTBS at 80% of AMT (but not at 90%) produced the opposite effect. These results are in contrast with what we observed in the present work and with previous studies using cerebellar TBS7.…”
Section: Discussionmentioning
confidence: 89%
“…Studies using 1 Hz rTMS applied over the cerebellum led to an increase of MEP amplitude (Oliveri et al, 2005; Fierro et al, 2007; Popa et al, 2010), thus suggesting a decrease of the Purkinje output to dentate nucleus and as a consequence disinhibition of the dentate-cortical drive. Harrington and Hammond (2015), however, have recently demonstrated that cTBS (delivered at low intensity, i.e., 80% of AMT) decreased the N100 waveform of the TMS-evoked potential, an indirect measure of cortical inhibition, and the resting MEP amplitude in the contralateral M1. These authors thus concluded that the effects of cTBS are likely exerted by inhibition of the superficial layer of the cerebellum (which has an inhibitory role on Purkinje cell activity).…”
Section: Discussionmentioning
confidence: 98%
“…FDIM1 and CRB: figure-of-eight (90 mm)Pre/Post 5, 25 minHC and PD: ↓ MEP↓ symptomsBologna et al (2015) [38]11 HC16 ETRight CRBSham (neck muscles)cTBS600 pulses80 % AMT2 randomizedRight FDIM1 and CRB: figure-of-eightPre/Post 5, 45 minHC: ↓ MEP RC ET: ↔ MEP RC ↔ symptomsBologna et al (2015) [37]10 HC13 RTIpsi. CRB to tremor handSham (neck muscles)cTBS600 pulses80 % AMT2 randomizedFDI (tremor hand)M1 and CRB: figure-of-eightPre/Post 5, 45 minHC and RT: ↓ MEP RC ↔ symptomsHarrington et al (2015) [39]13 HCRight CRBcTBSiTBSSham TBS600 pulses80 % AMT (6 subjects)90 % AMT (7 subjects)3randomizedcrossoverRight FDIM1 and CRB: figure-of-eightPre/PostcTBS: ↓ MEP AD Alzheimer’s disease, AMT active motor threshold, APB abductor pollicis brevis, CBI cerebellar brain inhibition, CBI RC cerebellar brain inhibition recruitment curve, CRB cerebellum, Contra contralateral, CSP cortical silent period, ET essential tremor, FDI first dorsal interosseous, HC healthy controls, ICF intracortical facilitation, Isps ipsilateral, LICI long interval intracortical inhibition, M1 primary motor cortex, MEP motor evoked potential, MEP RC motor evoked potential recruitment curve, MSO maximal stimulator output, PAS paired-associative stimulation, PCS posterior circulation stroke, PD Parkinson’s disease, PSP progressive supranuclear palsy, SAI short latency afferent inhibition, SAI RC short latency afferent inhibition recruitment curve, SICI short interval intracortical inhibition, SICF short interval intracortical facilitation, WD writing dystonia …”
Section: Introductionmentioning
confidence: 99%
“…Intracortical inhibitionSICIAnodal TDCSGalea et al (2009) [41]ISI: 2 msCS: 80 % RMTTS: 1 mV (adjusted post)Cathodal TDCSGalea et al (2009) [41]ISI: 2 msCS: 80 % RMTTS: 1 mV (adjusted post)1 Hz rTMSOliveri et al (2005) [30]ISI: 1 and 3 msCS: 70 % RMTTS: 1 mV (adjusted post)Fierro et al (2007) [31]ISI: 2 and 4 msCS: 80 % RMTTS: 120 % RMT (adjusted post)Langguth et al (2008) [47]ISI: 2, 3, 4 and 5 msCS: 90 % AMT, TS: 1 mV↑ (averaged ISIs)10 Hz rTMSLangguth et al (2008) [47]ISI: 2, 3, 4 and 5 msCS: 90 % AMT, TS: 1 mVcTBSKoch et al (2008) [34]ISI: 1, 2, 3, 4 and 5 msCS: 80 % AMT, TS: 1 mV↓ (3 ms, contralateral only)Carrillo et al (2013) [36]ISI: 1, 2, 3, 4 and 5 msCS: 80 % AMTTS: 1 mV↓ (2 and 3 ms, 0–20 min)Di Lorenzo et al (2013) [40]ISI: 1, 2, 3, 4 and 5 msCS: 80 % AMTTS: 1 mVHubsch et al (2013) [49]SI: 2.5 msCS: 70 % RMTTS: 130 % RMT (adjusted post)iTBSKoch et al (2008) [34]ISI: 1, 2, 3, 4 and 5 msCS: 80 % AMTTS: 1 mVCB-M1 PASLu et al (2012) [19]ISI: 2 msCS: 70 to 90 % AMT (50 % inh. )↓ (all PAS ISIs)LICITACSNaro et al (2016) [45]ISI: 50 msCS: 120 % RMTTS: 120 % RMTcTBSKoch et al (2008) [34]ISI: 100 and 150 msCS: 120 % RMTTS: 1 mV↑ (100 ms)Hubsch et al (2013) [49]SI: 100 msCS: 120 % RMTTS: 130 % RMT (adjusted post)iTBSKoch et al (2008) [34]ISI: 100 and 150 msCS: 120 % RMTTS: 1 mV↓ (100 ms)CSP1 Hz rTMSOliveri et al (2005) [30]30 % maximal forceTS: 1 mVcTBSHarrington et al (2015) [39]20 Newton forceTS:110 % RMT...…”
Section: Introductionunclassified
See 1 more Smart Citation